ANALISIS STRESOR KERJA, DUKUNGAN ORGANISASIONAL PERSEPSIAN, DAN JENDER TERHADAP WORK-FAMILY CONFLICT DAN FAMILY-WORK CONFLICT - TRI WIKANINGRUM (Jurnal Ekonomi dan Bisnis, 2010)
The current study examined the impact of perceived organizational support (POS), workstressor, and gender on work-family conflict (WFC) and family-work conflict (FWC) variables.The participants were 100 lecturers working full-time for a variety of universities in Semarang.T-test and hierarchical regression analysis were used to test the hypotheses. The resultindicated that POS was negatively related to both WFC and FWC. POS exhibited a moderatingeffect of the relationships of stressor and FWC, but not WFC. The result also indicated thatgender did not predict the level of conflict, and not moderated the effect of stressor on bothtypes of the conflict.Keywords: Pos, Stressor, Gender, WFC, FWC